Legal Discrimination in Settlement of Children's Cases as a Criminal Act Perpetrator - Zainal Arifin; Musmuliadin; Iksan (Bulletin of Community Engagement, 2026)
This article examines discrimination against children in conflict with the law, which remains a serious issue within the juvenile justice system, particularly due to the dominance of a retributive paradigm that positions children primarily as objects of punishment. The study aims to analyze the extent to which the restorative justice paradigm can function as an instrument to eliminate discrimination within the juvenile criminal justice system by emphasizing a comprehensive understanding of its fundamental principles. This research employs a qualitative method with a library-based research design, conducted through the analysis of national legislation, legal doctrines, and relevant international human rights instruments, including the Child Protection Law, the Juvenile Criminal Justice System Law, the United Nations Convention on the Rights of the Child, and the Universal Declaration of Human Rights. The findings indicate that, from a normative perspective, restorative justice is consistent with the principles of non-discrimination, the best interests of the child, and the protection of children’s rights as guaranteed under national and international legal frameworks. This paradigm not only provides an alternative mechanism through diversion but also offers a transformative framework to address and rectify retributive, stigmatizing, and potentially discriminatory tendencies within the juvenile justice system.